(untitled) (Jurnal Manajemen Bisnis, 2023)
The DPRD secretariat is a government organisation whose job it is to manage the DPRD’s finances and secretarial tasks, help the Provincial DPRD carry out its duties and functions, and provide and coordinate the experts the DPRD needs to carry out its rights and duties, such as running the DPRD secretariat, managing the DPRD’s finances, setting up meeting rooms, and providing and coordinating the experts. The digital world, lack of employee discipline, and the idea that work discipline hurts employee performance are some of the problems that show up in the West Sulawesi Provincial DPRD office. The researcher wants to look into the factors that affect how well employees do their jobs in the DPRD office in West Sulawesi Province based on their digital work setting. A qualitative study method was used, and direct interviews were used to get the first-hand information. The people who answered are workers. The Proportional Random sampling method was used to pick samples, and 4 employees were interviewed for each group. A method of analysing the interview data that involved asking direct questions was used. From the interviews, we learned that the variables in the digital environment, work discipline, and employee performance all had some impact on how well the DPRD Office of West Sulawesi Province workers did their jobs.